Answer:
[tex]y= -\frac76x +1[/tex]; [tex]y= \frac67x -\frac{78}7[/tex]
Step-by-step explanation:
We know from theory that two perpendicular lines have the product of their slope equal to -1. Let's find the second slope:
[tex]\frac67m = -1 \rightarrow m=-\frac76[/tex]
At this point we can just use the slope-point equation to get our first line:
[tex]y-y_0 = m(x-x_0)\\y-(-6) = -\frac76(x-6) \\y+6= -\frac76x +7\\y= -\frac76x +1[/tex]
Now, we know that two parallel lines have the same slope. Time to apply the same point-slope formula, with the original m this time.
[tex]y-(-6) = \frac67(x-6)\\y+6 = \frac67x -\frac{36}7\\y= \frac67x -\frac{36}7 -{\frac{42}7[/tex]
[tex]y= \frac67x -\frac{78}7[/tex]